MRI Cartilage Assessment of the Subtalar and Midtarsal Joints During a Transcontinental Ultramarathon – New Insights into Human Locomotion - Schütz, Uwe Hans-Werner; Billich, Christian; Schoss, Daniel; Beer, Meinrad; Ellermann, Jutta (International Journal of Sports Medicine, 2018)
MR measurements can be accurately performed during 4486 km of running, opening a window into in vivo assessment of hindfoot articular cartilage under extreme ultra-endurance loading. This observational cross-sectional study included 22 randomized participants of TransEurope FootRace between Italy and the North Cape, which was accompanied by a trailer-mounted 1.5T MRI scanner over 9 weeks. Four follow up MR examinations of subtalar and midtarsal joints were performed. Statistics of cartilage T2*  and thickness were obtained. Nearly all observed joints showed an initial significant mean T2*  increase of 20.9% and 26.3% for the left and right side, followed by a relative decrease of 28.5% and 16.0% during the second half, respectively. It could be demonstrated that mobile MRI field studies allow in vivo functional tissue observations under extreme loading. Elevated T2*  values recovered during the second half of the ultramarathon supported the evidence that this response is a physiological adaptive mechanism of chondrocyte function via upregulation of de novo synthesis of proteoglycans and collagen. These changes occurred in a distinct asymmetric pattern leaving a “biochemical signature” of articular cartilage that allows in vivo insight into joint loading. In conclusion, the normal articular cartilage of the hindfoot is resilient and adaptive, leaving extreme endurance activities up to limitless human ambition.
Keywords: functional magnetic resonance imaging; foot; running; marathon; mapping; chondral, cartilage